The Reaction of Capital Markets on the 2024 Presidential Election (An Event Study of Companies in the Infrastructure Sector and Building Construction Sub-Sector Listed on the Indonesia Stock Exchange) - Prasintahayu, Elysa; Indrawati, Nur Khusniyah (Jurnal Management Risiko dan Keuangan, 2025)
Purpose – This study aims to analyze the reaction of the capital market to the 2024 Indonesian presidential election in the infrastructure and building construction sub-sector listed on the Indonesia Stock Exchange.     Design/methodology/approach – This research uses a quantitative event study approach. The sample consists of 17 companies selected through purposive sampling, specifically firms categorized in the green zone according to Refinitiv. Data were obtained from documentation sources, with variables including abnormal return and trading volume activity.   Findings – The results show that there is no significant difference in average abnormal return before and after the 2024 presidential election. However, there is a significant difference in average trading volume activity before and after the election.   Originality/value – This study contributes to event study literature by providing empirical evidence on how political events influence capital market behavior in the Indonesian infrastructure and construction sector.